2019
DOI: 10.3390/biom9110733
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for the Biosynthesis of Short Oligopeptides: Green and Sustainable Chemistry

Abstract: Short oligopeptides are some of the most promising and functionally important amide bond-containing components, with widespread applications. Biosynthesis of these oligopeptides may potentially become the ultimate strategy because it has better cost efficiency and environmental-friendliness than conventional solid phase peptide synthesis and chemo-enzymatic synthesis. To successfully apply this strategy for the biosynthesis of structurally diverse amide bond-containing components, the identification and select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…The γ-lactam moiety of 1−4 could be derived from two molecules of amino acids (homoserine with leucine, (R)-2-amino-5-methylhex-5-enoic acid, phenylalanine, and tyrosine, respectively) catalyzed by nonribosomal peptide synthetase (NRPS), followed by a series of reactions including oxidation, dehydration, intramolecular condensation, reduction, and methylation as illustrated in Scheme 1. 53,54 Biological Activity. The antibacterial activities of all compounds were evaluated.…”
Section: Molecularmentioning
confidence: 99%
“…The γ-lactam moiety of 1−4 could be derived from two molecules of amino acids (homoserine with leucine, (R)-2-amino-5-methylhex-5-enoic acid, phenylalanine, and tyrosine, respectively) catalyzed by nonribosomal peptide synthetase (NRPS), followed by a series of reactions including oxidation, dehydration, intramolecular condensation, reduction, and methylation as illustrated in Scheme 1. 53,54 Biological Activity. The antibacterial activities of all compounds were evaluated.…”
Section: Molecularmentioning
confidence: 99%
“…Thus, bio-herbicides from natural sources are required. DKPs are promising nature-inspired herbicides due to their environmental friendliness, safety, high selectivity, and probable new target sites [322][323][324]. Proline-derived DKPs have specific herbicide activities [32].…”
Section: Activators Of Dioxygen In Oxidative Processesmentioning
confidence: 99%
“…It was also hypothesized that biological activity of short sequence peptides is associated with their prominent antioxidant properties, although this data is contradictory as some oligopeptides were reported to have prooxidant effect. A number of studies have demonstrated the effect of short peptides on the proliferation and differentiation of stem cells [14,33]. Several oligopeptides were reported to exert potent geroprotective effect due to the inhibition of apoptosis, induction of telomerase activity and telomere elongation in human fibroblast culture, which can be due to reactivation of the telomerase gene in somatic cells and indicates the possibility of prolonging the life span of a cell population [33].…”
Section: The Mechanism Of Action Of Short Sequence Peptidesmentioning
confidence: 99%
“…A number of studies have demonstrated the effect of short peptides on the proliferation and differentiation of stem cells [14,33]. Several oligopeptides were reported to exert potent geroprotective effect due to the inhibition of apoptosis, induction of telomerase activity and telomere elongation in human fibroblast culture, which can be due to reactivation of the telomerase gene in somatic cells and indicates the possibility of prolonging the life span of a cell population [33].…”
Section: The Mechanism Of Action Of Short Sequence Peptidesmentioning
confidence: 99%